PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Sarmini, ; Sunarmi, (Pendidikan Ekonomi, 2012)
The implementation of problem based instruction model is aimed to enhaching students motivation and learing outcomes especially in materials price index and inflation. The results showed that teacher managing learning activity has increased in every sycle. In this case, increasing capabilities teacher on managing learning activity to be able to enhaching students motivation and learing outcomes. Student learning outcomes also increased. It is because every student can understand the problem of inflation and ways to evercome them thoroughly problem based instruction model. The students motivation also increased. Problem based instruction model allowed student to understand the problems of inflation and price index in realterms.